Effect of Cu, Ag on the microstructure and IMC evolution of Sn5Sb–CuAgNi/Cu solder joints. (17th May 2019) - Han, Bangyao; Sun, Fenglian; Ban, Gaofang; Liu, Yang; Liu, Yang; Li, Tianhui; Pang, Shushui
Abstract: In this paper, three new type Sn5Sb-based solders were used to the study. The three sets of solders are Sn–5Sb–0.5Cu–0.1Ni–0.5Ag, Sn–5Sb–0.5Cu–0.1Ni–0.1Ag and Sn–5Sb–1Cu–0.1Ni–0.1Ag. Experimental results indicated that with the increase of Cu and Ag, the solidus temperature reduced due to the increase of the eutectic phase of low melting point Ag3 Sn+ β -Sn and Cu6 Sn5 + β -Sn in the solder. The adding elements of Cu, Ni, Ag can improve the wettability of Sn5Sb while excessive Cu, Ag content inhibit the wettability. The Similar microstructures exist in the three groups of solders, which consist of β -Sn–Sb solid solutions, (Cu1−x Nix)6 Sn5, Ag3 Sn and a small amout of β -Sn. The interfacial intermetallic compound (IMC) is composed of (Cu1−x Nix)6 Sn5 . The lower Cu content suppresses the IMC growth by increasing the dissolution of interfacial IMCs into bulk solder but it also increase the IMC growth by elevating the diffusion speed. The thickness of the IMC layer of Sn–5Sb–0.5Cu–0.1Ni–0.1Ag/Cu grow faster than that of Sn–5Sb–1Cu–0.1Ni–0.1Ag/Cu, Which illustrates the Cu atoms affect the IMC mainly through inhibiting the reaction diffusion. The addition of Ag in the solder significantly suppressed the IMC layer in Sn–5Sb–0.5Cu–0.1Ni–0.5Ag/Cu, Which is attributes to the concentration of Ag3 Sn near the IMC layer. The increase of Cu, Ag content in the solder will increase the ductility of the solder. The toughness decrease when the liquid keeping time over 30 s and the shear strength decrease correspondingly. The fracture mechanism changed from ductile fracture to tough and brittle hybrid fracture when the liquid keeping time from 10 s to 90 s.